Diaphragm and preparation method and application thereof

By using a hybrid coating layer design of PMMA particles and inorganic particles in the lithium-ion battery separator, the problems of high equipment requirements and high cost in the prior art are solved, the high breakdown strength and yield of the separator are achieved, and the battery cell is reduced Short-circuit rate and production cost enhance the insulation performance of the diaphragm.

CN119208919APending Publication Date: 2024-12-27SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411429843.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The method of improving the breakdown strength of the lithium-ion battery separator in the prior art usually requires high equipment costs or affects the insulation performance of the separator, and it is difficult to improve the breakdown resistance of the separator while reducing equipment requirements and controlling costs.

Method used

Using a separator design including a base film and a coating layer, the coating layer contains PMMA particles, inorganic particles, butyndecyl glycol ethoxylate modified polysiloxane, aqueous binder and thickener, by controlling PMMA The ratio of particle size to coating layer thickness and coating layer porosity is formed to form an efficient hybrid coating layer to enhance the breakdown strength of the membrane.

Benefits of technology

It realizes that without increasing equipment requirements and cost reduction, significantly improves the breakdown voltage and production yield of the diaphragm, reduces the short-circuit rate of the cell Hipot, enhances the insulation performance of the diaphragm, and reduces the amount of wetting agent to avoid penetration into the base film. , improve the safety and production efficiency of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208919A_ABST
    Figure CN119208919A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to a diaphragm as well as a preparation method and application thereof. According to the diaphragm provided by the invention, by selecting the wetting agent in the coating layer, limiting the dosage of the wetting agent and limiting the proportional relation between the particle size D of the PMMA particles and the thickness H of the coating base layer, the breakdown strength of the diaphragm is improved, and meanwhile, the influence of the wetting agent on the insulating property of the diaphragm is avoided. In addition, compared with a conventional layered multi-time coating diaphragm with a base film, a heat-resistant coating and a bonding coating, through the mixed coating mode of inorganic particles and large-particle PMMA, the simplification of the coating layer is realized, the bonding and heat-resistant requirements on the coating layer are met, the production cost of the diaphragm is reduced, and the requirement on production equipment is not higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a diaphragm and a preparation method and application thereof. Background Art

[0002] With the vigorous development of the new energy industry, the lithium-ion battery manufacturing field has made rapid progress. Improving the yield of battery cell production and achieving cost reduction and efficiency improvement in battery manufacturing have great practical significance. Lithium-ion battery separator is one of the four main materials of lithium-ion batteries, which plays the role of isolating the positive and negative electrodes and preventing them from contacting and causing short circuits.

[0003] During the manufacturing process of battery cells, short circuits are usually caused by punctures in the diaphragm or breakdown by voltage. The causes of short circuits in the Hipot test (also known as high-voltage insulation test or voltage resistance test) can be divided into two categories: ① The diaphragm itself has weak points and is punctured by foreign objects, resulting in short circuits caused by contact between the positive and negative electrodes. At present, as the thickness of the diaphragm base film becomes thinner, its ability to resist foreign objects decreases, making it easier for the diaphragm to be punctured; ② During the multiple coating processes of the diaphragm, the wetting agent used in the coating penetrates into the microporous structure of the base film, resulting in a significant decrease in the intrinsic insulation performance of the diaphragm and a decrease in the breakdown voltage, which makes it easy to cause a short circuit in contact between the positive and negative electrodes in the battery Hipot test, posing a threat to the safety of the battery cell.

[0004] The existing way to improve the breakdown resistance of the diaphragm, from the perspective of the base membrane, is mainly to optimize the process technology of the base membrane, improve the pore size consistency of the base membrane, reduce the generation of larger pores, and reduce the risk of breakdown. This method places higher requirements on the stretching equipment of the diaphragm and requires equipment upgrades and iterations. From the coating perspective, it is mainly to use some breakdown-resistant coating materials such as aramid to increase the overall breakdown voltage of the diaphragm, but the coating method is mostly oily coating and the cost is relatively high, which is not conducive to large-scale promotion and application. The conventional layered coating (heat-resistant inorganic coating + adhesive organic coating) solution requires the use of a wetting agent in each coating process, which increases the risk of penetrating into the micropores of the base membrane and also causes a decrease in the insulation performance of the diaphragm.

[0005] In summary, it is of great significance to provide a method for improving the breakdown strength of the diaphragm which has low equipment requirements, low cost, and does not affect the insulation performance of the diaphragm. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present application is to overcome the defects of the prior art methods for improving the breakdown strength of the diaphragm, such as high equipment requirements, high cost or impact on the insulation performance of the diaphragm, thereby providing a diaphragm and its preparation method and application.

[0007] To this end, this application provides the following technical solutions:

[0008] According to one aspect of the present application, a diaphragm is provided, comprising: a base film and a coating layer located on at least one surface of the base film, wherein the coating layer comprises a coating base layer and PMMA (polymethyl methacrylate) particles dispersed in the coating base layer;

[0009] The coating base layer comprises inorganic particles, butynediol ethoxylate modified polysiloxane, a water-based binder and a thickener;

[0010] The particle size D of the PMMA particles and the thickness H of the coating base layer satisfy the following relationship: 6≥D / H≥1.5.

[0011] In the present application, the butynediol ethoxylate modified polysiloxane is obtained by subjecting butynediol ethoxylate (CAS No. 1606-85-5) and polysiloxane (number average molecular weight of 900-11000) to a hydrosilylation reaction at 70-90° C. in an inert atmosphere for 10-14 hours.

[0012] In some optional embodiments, the mass ratio of butynediol ethoxylate to polysiloxane is 1:(5-8).

[0013] In some optional embodiments, the porosity of the coating layer is 40%-50%.

[0014] In some optional embodiments, based on the total mass of the coating layer, the mass percentage of the wetting agent is 0.15%-0.25%.

[0015] In some optional embodiments, based on the total mass of the coating layer, the mass percentage of the PMMA particles is 4%-8%;

[0016] And / or, the mass percentage of the inorganic particles is 85.5%-89.5%;

[0017] And / or, the mass percentage of the thickener is 1%-1.5%;

[0018] And / or, the mass percentage of the aqueous binder is 4.5%-5.3%.

[0019] In some optional embodiments, the breakdown voltage of the diaphragm is K1, in V, the breakdown voltage of the base film is K2, in V, and the thickness of the coating layer is H, in μm, and the following relationship is satisfied:

[0020] 100≤(K1-K2) / H≤200.

[0021] In some optional embodiments, the particle size Dv50 of the inorganic particles is below 300 nm;

[0022] And / or, the base film has a thickness of 3-20 μm;

[0023] And / or, the thickness H of the coating base layer is 1-3 μm.

[0024] In some optional embodiments, the inorganic particles include but are not limited to at least one of alumina and boehmite;

[0025] And / or, the aqueous adhesive includes but is not limited to at least one of an acrylic adhesive or styrene-butadiene adhesive;

[0026] and / or, the thickener includes but is not limited to sodium carboxymethyl cellulose;

[0027] And / or, the base film includes but is not limited to at least one of a polyethylene base film and a polypropylene base film.

[0028] According to another aspect of the present application, a method for preparing the above-mentioned diaphragm is provided, comprising the following steps:

[0029] S1, mixing inorganic particles, PMMA particles, a thickener, an aqueous binder, butynediol ethoxylate-modified polysiloxane and water to obtain a slurry;

[0030] S2, coating the slurry onto at least one surface of the base film, and drying to obtain the diaphragm.

[0031] In the present application, the coating method of the slurry is conventional in the art. Typically, but not limiting, the slurry is coated on one or both sides of the base film by gravure roller coating and dried at 70-90°C.

[0032] In step S1, there is no specific limitation on the solid content of the slurry, as long as it is suitable for roller coating operation.

[0033] According to another aspect of the present application, a secondary battery is provided, comprising the above-mentioned separator or the separator prepared by the above-mentioned preparation method.

[0034] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.

[0035] The secondary battery provided in the present application also includes a positive electrode sheet, a negative electrode sheet and an electrolyte. The present application does not specifically limit the preparation method of the secondary battery, and the secondary battery can be prepared by a conventional preparation method in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery cell is obtained by a stacking or winding process, and then the secondary battery of the present application can be obtained through baking, injection, formation, packaging and other processes.

[0036] According to another aspect of the present application, there is provided an electric device, comprising the secondary battery provided above. The secondary battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0037] The technical solution of this application has the following advantages:

[0038] The diaphragm provided in the present application comprises: a base film and a coating layer located on at least one side of the base film, wherein the coating layer comprises a coating base layer and PMMA particles dispersed in the coating base layer; the coating base layer comprises inorganic particles, butynediol ethoxylate modified polysiloxane, an aqueous binder and a thickener; the particle size D of the PMMA particles and the thickness H of the coating base layer satisfy the following relationship: 6≥D / H≥1.5. The diaphragm provided in the present application improves the breakdown strength of the diaphragm and reduces the number of electrical weak points of the diaphragm by selecting a wetting agent in the coating layer and limiting the proportional relationship between the particle size D of the PMMA particles and the thickness H of the coating base layer; the battery cells produced using this diaphragm have a lower Hipot short circuit rate and a higher production yield. In addition, compared with the conventional base film + heat-resistant coating + bonding coating layered multiple coating diaphragm, the method of forming a mixed coating layer by inorganic particles and large PMMA particles realizes the simplification of the coating layer, while meeting the bonding and heat resistance requirements of the coating layer, reducing the production cost of the diaphragm, and there is no higher requirement for the production equipment. Specifically, as a component that plays the role of bonding the diaphragm and the pole piece, the large PMMA particles need to be in contact with the pole piece surface as contact sites during the hot pressing process, so their particle size needs to be slightly higher than the coating base layer to better play the bonding role during the hot pressing process. If the particle size of the PMMA particles is too large, it is easy to fall off, and if the particle size is too small, it is easy to cause PMMA to be completely embedded in the coating base layer, or too little part of the coating base layer surface is exposed, thereby affecting the bonding effect. By using butynediol ethoxylate modified polysiloxane as a wetting agent, the dispersion and wetting ability of the slurry is improved, the penetration of the wetting agent in the base film gap is reduced, and its adverse effect on the breakdown resistance of the diaphragm is avoided.

[0039] The diaphragm provided by the present application has a mass percentage of the wetting agent of 0.15%-0.25% based on the total mass of the coating layer. The present application can further reduce the amount of the wetting agent used in the slurry compared to conventional wetting agents through the selection of the wetting agent, so as to avoid the increased risk of the wetting agent penetrating into the pores of the base film due to excessive use of the wetting agent, thereby adversely affecting the breakdown resistance of the diaphragm.

[0040] The diaphragm provided in the present application has a porosity of 40%-50%. By limiting the porosity of the coating layer to a certain range, the breakdown voltage of the coating layer can be further improved. Since the diaphragm is essentially breaking down the air in the pores of the diaphragm under voltage during the breakdown process, a high porosity makes it easier to be broken down, which will cause the voltage resistance of the diaphragm to decrease; if the porosity is too low, the pore blocking effect of the coating increases, and the permeability of the diaphragm increases (the permeability in this application refers to the time required for a fixed volume of air to pass through the diaphragm, and the value of the permeability is inversely proportional to the porosity, the lower the porosity, the higher the permeability), which may affect the performance of the battery cell and cause the internal resistance of the battery cell to increase. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0042] Figure 1 is a schematic diagram of the structure of the diaphragm provided in the embodiment of the present application;

[0043] Reference numerals:

[0044] 1. Base film; 2. Coating layer; 3. PMMA particles; 4. Coating base layer. DETAILED DESCRIPTION

[0045] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0047] Example 1

[0048] This embodiment provides a diaphragm, and its structural schematic diagram is as follows Figure 1 As shown, the figure only shows the structure of one side of the base film 1, including the base film 1 and the coating layer 2, the coating layer 2 includes a coating base layer 4 and PMMA particles 3 dispersed in the coating base layer 4. The specific preparation method includes the following steps:

[0049] (1) Inorganic particles (boehmite, particle size D50 = 200 nm), PMMA particles (Shenzhen Haodian, particle size see Table 1), thickener (sodium carboxymethyl cellulose), aqueous binder (acrylic binder, brand Haodian SWA610) and butynediol ethoxylate modified polysiloxane (obtained by hydrosilylation reaction of butynediol ethoxylate and polysiloxane (number average molecular weight 2012) in a mass ratio of 1:6 at 80°C under an inert atmosphere for 12 h) were added to deionized water in a mass ratio of 87.5:6:1.3:5:0.2 to prepare a slurry;

[0050] (2) The slurry is coated on both sides of a 9 μm thick conventional porosity PE base membrane (porosity 40%) by gravure roller coating. The thickness of the single layer coating is controlled to be 1 μm. The slurry is dried at 80° C. and baked for 3 minutes to obtain the diaphragm. The diaphragm structure is 9+1+1.

[0051] Example 2

[0052] This embodiment provides a diaphragm, which is different from the embodiment 1 only in that the single-layer coating thickness is 2 μm and the diaphragm structure is 9+2+2.

[0053] Example 3

[0054] This embodiment provides a diaphragm, which is different from the embodiment 1 only in that the single-layer coating thickness is 3 μm and the diaphragm structure is 9+3+3.

[0055] Example 4

[0056] This embodiment provides a diaphragm, which is different from Embodiment 2 in that the slurry is coated on one side of a PE-based membrane with a conventional porosity of 9 μm in thickness by gravure roller coating, and the diaphragm structure is 9+2.

[0057] Example 5

[0058] This embodiment provides a diaphragm, which is different from Embodiment 4 only in that, based on the mass ratio of the effective ingredients, the mass ratio of the inorganic particles, PMMA particles, thickener, aqueous binder and butynediol ethoxylate-modified polysiloxane in the slurry is 87.45:6:1.3:5:0.25.

[0059] Example 6

[0060] This embodiment provides a diaphragm, which is different from Embodiment 4 only in that, based on the mass ratio of the effective ingredients, the mass ratio of the inorganic particles, PMMA particles, thickener, aqueous binder and butynediol ethoxylate-modified polysiloxane in the slurry is 87.55:6:1.3:5:0.15.

[0061] Comparative Example 1

[0062] This comparative example provides a diaphragm, and its specific preparation method is as follows:

[0063] In the first step, inorganic particles (boehmite, D50 is 200nm), thickener, aqueous binder and wetting agent are added to deionized water in a mass ratio of 93.5:1:5:0.5 according to the mass ratio of the active ingredients to prepare the diaphragm coating slurry. The slurry is coated on both sides of the 9μm regular porosity PE base film by gravure roller coating, the coating thickness is controlled to be 2μm, and the drying treatment is carried out at 80℃ for 3min;

[0064] In the second step, PVDF (commercially available: Arkema LBG), thickener, aqueous binder and wetting agent are added to deionized water in a mass ratio of 93:1:5:1 according to the mass ratio of the active ingredients to prepare a membrane coating slurry. The slurry is coated on the surface of the semi-finished product obtained in the first step by gravure roller coating, the coating thickness is controlled to be 1 μm, and the membrane is dried at 80°C for 3 minutes to obtain the membrane of the present invention, and the membrane structure is 9+2+2+1+1.

[0065] Comparative Example 2

[0066] This comparative example provides a diaphragm, and its specific preparation method is as follows:

[0067] In the first step, inorganic particles (boehmite, D50 is 200nm), thickener, aqueous binder and wetting agent are added to deionized water in a mass ratio of 93.5:1:5:0.5 according to the mass ratio of the active ingredients to prepare the diaphragm coating slurry. The slurry is coated on one side of the 9μm conventional porosity PE base film by gravure roller coating, the coating thickness is controlled to be 2μm, and the drying treatment is carried out at 80℃ for 3 minutes.

[0068] In the second step, according to the mass ratio of the active ingredients, PVDF, thickener, aqueous binder and wetting agent are added to deionized water in a mass ratio of 93:1:5:1 to prepare a membrane coating slurry. The slurry is coated on one side of the semi-finished product obtained in the first step by gravure roller coating, the coating thickness is controlled to be 1 μm, and the membrane is dried at 80°C for 3 minutes to obtain the membrane of the present invention, and the membrane structure is 9+2+1.

[0069] Comparative Example 3

[0070] This comparative example provides a diaphragm, which is different from Example 1 only in that the ratio of D / H is too large, as shown in the table below.

[0071] Comparative Example 4

[0072] This comparative example provides a diaphragm, which is different from Example 1 only in that the ratio of D / H is too small, as shown in the table below.

[0073] Comparative Example 5

[0074] This comparative example provides a diaphragm, which is different from Example 1 only in that an equal mass of conventional wetting agent lauryl alcohol polyether (Tianjin Saipu Rui E1206) is used to replace the wetting agent in the above example.

[0075] Test Case

[0076] 1. Short circuit rate test

[0077] The diaphragms provided in the embodiments and comparative examples are used to prepare lithium-ion batteries, and the preparation method is as follows:

[0078] First, preparation of positive electrode sheet: lithium iron phosphate is used to prepare slurry, and the slurry is coated on carbon-coated aluminum foil to obtain positive electrode sheet. Lithium iron phosphate accounts for 96% of the coating, conductive carbon black 1.5%, PVDF adhesive 2%, dispersant 0.5%, and the single-side coating surface density is 20mg / cm 2 .

[0079] Second, the preparation of negative electrode sheet: artificial graphite is used to prepare slurry, and the slurry is coated on the copper foil to make the negative electrode sheet after treatment. Artificial graphite accounts for 95.5% of the coating, conductive carbon black conductive agent 1.5%, SBR adhesive 3%, and the single-side coating surface density is 9mg / cm 2 .

[0080] Preparation of lithium-ion batteries: The prepared negative electrode plates, positive electrode plates, separators, and electrolytes (the electrolyte is a conventional electrolyte containing EC / EMC / DMC solvents in a volume ratio of 1:1:1 and 1 mol / L lithium salt LiPF6) are assembled into 4Ah soft-pack cells, with 1,000 cells assembled in each group. The electrode group Hipot test is performed and the short-circuit rate is calculated.

[0081] 2. Electrical weakness test

[0082] The diaphragms prepared in the embodiments and comparative examples were subjected to a diaphragm electrical weakness test: the test voltage was 1500V, the test diaphragm length was 50m, the test speed was 3m / min, the number of breakdown points was counted, and the number of electrical weakness points per square meter was calculated.

[0083] 3. Breakdown strength test

[0084] The diaphragms prepared in each embodiment and comparative example were subjected to a diaphragm breakdown strength test, and the test method was referred to GB / T36363-2018.

[0085] 4. Coating thickness test

[0086] The membrane cross section was tested using a SEM electron microscope to measure the coating thickness.

[0087] 5. Porosity of coating layer

[0088] The porosity of the coating layer is calculated by using the true density of the inorganic material and the actual surface density and thickness of the coating. The porosity of the coating layer = 1 - surface density of the coating / (true density of the coating material × coating thickness).

[0089] 6. Insulation resistance

[0090] DC withstand voltage test: The insulation resistance meter starts the test, outputs high voltage (150V) and applies it to the product under test, then detects the leakage current flowing through the product under test, and calculates the insulation resistance value based on Ohm's law: R=U / I. The table shows the average value of 1000 samples.

[0091] 7. Adhesion

[0092] After the two layers of diaphragms were hot-pressed at 90°C, the adhesion between the diaphragms was tested using a stretching machine.

[0093] The specific test results are shown in the table below:

[0094] Table 1

[0095]

[0096] Table 2

[0097]

[0098]

[0099] From the data in the above table, it can be seen that the breakdown voltage of the diaphragm provided by the embodiment of the present application is greatly improved compared with the existing conventional diaphragm, the number of electrical weaknesses is greatly reduced, the hipot short circuit rate of the battery cell production process is lower, the production yield is higher, and the diaphragm production cost is more advantageous. Compared with the existing water-based layered coating diaphragm, one coating process is reduced, the diaphragm cost is lower, and the amount of wetting agent used in the coating is reduced, and the wetting agent is reduced. The penetration of the base film causes the reduction in the breakdown voltage of the diaphragm. Specifically, by comparing Example 2 with Comparative Example 1 and Example 4 with Comparative Example 2, it can be found that the coating layer porosity of the diaphragm provided by the embodiment of the present application is 40-50%, and the average breakdown voltage can reach more than 1650V, and the highest can reach 2354V. Compared with the conventional layered coating diaphragm, its coating porosity is more than 50%, and the average breakdown voltage is about 1500V. At the same time, the results of using 1500V voltage to test the electrical weaknesses of the diaphragm show that the diaphragm provided by the embodiment of the present application has fewer electrical weaknesses, stronger insulation ability, and is less likely to be broken down. By comparing the short-circuit rate of the pole group after hot pressing of the battery cells prepared in each group, it can be seen that the short-circuit rate of the pole group obtained after the assembly of the diaphragm of each embodiment is lower than that of the conventional layered coating diaphragm, and the production yield is higher. By comparing the data of Examples 1-3, it can be seen that as the thickness of the heat-resistant coating increases, the breakdown voltage increases, the number of electrical weaknesses of the diaphragm is smaller, and the insulation capacity is stronger. By comparing Comparative Example 2 and Examples 4-6, it can be seen that compared with the layered coating method, the simplified coating method of the mixed coating in the embodiment reduces the slurry coating once, from two times to one time, and the polysiloxane dispersed wetting effect modified by butynediol ethoxylate used is better than the conventional wetting agent, and the proportion of the amount used in the coating can be reduced from 0.5% to 0.15-0.25%, reducing the amount of wetting agent used. Within the use ratio range, as the amount of wetting agent used in the coating decreases, the penetration of wetting in the pore size of the base membrane is reduced, and the reduction in the breakdown voltage of the diaphragm caused by the penetration of the wetting agent into the base membrane is reduced. From the data of Comparative Examples 3-4, it can be seen that only by limiting the relationship D / H between PMMA particle size and inorganic coating thickness within a specific range can the coating layer and the base film have good adhesion and meet the use requirements. If the particle size D is too large, it is easy to fall off, affecting the adhesion; if the particle size is too small, it is easy to cause too much PMMA to be embedded in the coating and too little to be exposed on the surface, thus affecting the bonding effect. At the same time, by means of mixed coating, the coating materials for achieving heat resistance and bonding are combined in the same coating for coating. While meeting the requirements of improving the high temperature resistance of the diaphragm, the adhesion of the diaphragm to the electrode can also be guaranteed, reducing the coating process, which may reduce the energy consumption cost of manufacturing and achieve material cost reduction.

[0100] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A diaphragm, characterized in that: include: A base film and a coating layer located on at least one side of the base film, wherein the coating layer comprises a coating base layer and PMMA particles dispersed in the coating base layer; The coating base layer comprises inorganic particles, butynediol ethoxylate modified polysiloxane, a water-based binder and a thickener; The particle size D of the PMMA particles and the thickness H of the coating base layer satisfy the following relationship: 6≥D / H≥1.

5.

2. The diaphragm according to claim 1, characterized in that The porosity of the coating layer is 40%-50%.

3. The diaphragm according to claim 1, characterized in that Based on the total mass of the coating layer, the mass percentage of the wetting agent is 0.15%-0.25%.

4. The diaphragm according to claim 1, characterized in that The mass percentage of the PMMA particles is 4%-8% based on the total mass of the coating layer; And / or, the mass percentage of the inorganic particles is 85.5%-89.5%; And / or, the mass percentage of the thickener is 1%-1.5%; And / or, the mass percentage of the aqueous binder is 4.5%-5.3%.

5. The diaphragm according to any one of claims 1 to 4, characterized in that: The breakdown voltage of the diaphragm is K1, in V, the breakdown voltage of the base film is K2, in V, and the thickness of the coating layer is H, in μm, which satisfy the following relationship: 100≤(K1-K2) / H≤200.

6. The diaphragm according to claim 5, characterized in that The particle size Dv50 of the inorganic particles is below 300 nm; And / or, the base film has a thickness of 3-20 μm; And / or, the thickness H of the coating base layer is 1-3 μm.

7. The diaphragm according to any one of claims 1 to 4, characterized in that: The inorganic particles include at least one of alumina and boehmite; And / or, the aqueous adhesive comprises at least one of an acrylic adhesive or styrene-butadiene adhesive; and / or, the thickener comprises sodium carboxymethyl cellulose; And / or, the base film includes at least one of a polyethylene base film and a polypropylene base film.

8. A method for preparing a diaphragm according to any one of claims 1 to 7, characterized in that: The steps include: S1, mixing inorganic particles, PMMA particles, a thickener, an aqueous binder, butynediol ethoxylate-modified polysiloxane and water to obtain a slurry; S2, coating the slurry onto at least one surface of the base film, and drying to obtain the diaphragm.

9. A secondary battery, characterized in that: The invention comprises the diaphragm according to any one of claims 1 to 7 or the diaphragm prepared by the preparation method according to claim 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Preparation method of alkynediol ethoxide modified polysiloxane

    CN104910384A

  • Separator including functional layer for electrochemical element, and electrochemical element

    CN113906626A

  • Ceramic composite diaphragm and lithium ion battery

    CN114374052A

  • Inorganic coating battery diaphragm, preparation method thereof and battery

    CN115275519A

  • Multifunctional composite coating diaphragm, preparation method and application in lithium battery

    CN117317514A

Cited By

  • Separator, and preparation method therefor and use thereof

    WO2026082045A1